2017
DOI: 10.1039/c6ta08659d
|View full text |Cite
|
Sign up to set email alerts
|

A novel LiCoPO4-coated core–shell structure for spinel LiNi0.5Mn1.5O4 as a high-performance cathode material for lithium-ion batteries

Abstract: A novel LiNi0.5Mn1.5O4@LiCoPO4 structure can improve the electrochemical performance by inducing an appropriate amount of Mn3+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…[55] Figures 5a 2 , 5b 2 and 5c 2 show the high resolution core spectra of Mn 2p 3/2 and the fitted peaks for the LMNÀSi/Nix with x = 0, 0.25 and 0.45, respectively. [58] In our work, more Mn 3 + may exist on the surface of the spinel materials rather than inside the structure. The ratios of the peak area of Mn 3 + /Mn 4 + are 3.86 : 1, 0.65 : 1 and 0.08 : 1 for the materials with x = 0, 0.25 and 0.45, respectively.…”
Section: Chemical Valence Analysismentioning
confidence: 65%
See 1 more Smart Citation
“…[55] Figures 5a 2 , 5b 2 and 5c 2 show the high resolution core spectra of Mn 2p 3/2 and the fitted peaks for the LMNÀSi/Nix with x = 0, 0.25 and 0.45, respectively. [58] In our work, more Mn 3 + may exist on the surface of the spinel materials rather than inside the structure. The ratios of the peak area of Mn 3 + /Mn 4 + are 3.86 : 1, 0.65 : 1 and 0.08 : 1 for the materials with x = 0, 0.25 and 0.45, respectively.…”
Section: Chemical Valence Analysismentioning
confidence: 65%
“…It can be seen that the Mn 2p 3/2 region for the LMNÀSi/Ni-x with x = 0, 0.25 and 0.45 consists of two peaks (at~642 eV and 643 eV), [56,57] indicating the coexistence of Mn 3 + and Mn 4 + in the LMNÀSi/Ni-xmaterials. [58][59][60][61] Thus, the fitted value of Mn 3 + for LMNÀSi/Ni-0 may be higher than the percentages of the Mn 4 + content. The XPS measurement is mainly used to analyze the element states on the surface.…”
Section: Chemical Valence Analysismentioning
confidence: 97%
“…[35] A further Mn3s edge analysis can be more direct evidence for the nominal valence states of Mn for the MnO 2 . [32,41,42] Figure 3a presents the XPS spectra of Mn 3s for the sample cycled at different potential windows. The average oxidation state (AOS) of Mn can be calculated by the distance between the two peaks in the XPS spectra of Mn 3s according to the following formula:AOS = 8.956 − 1.126ΔE, where ΔE indicates the distance between the two peaks.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the XPS spectrum of Mn 2p includes two sets of characteristic peaks: Mn 2p 1/2 and Mn 2p 3/2 , which are caused by spin–orbital splitting. And the peak of Mn 2p 3/2 can be deconvoluted and ascribed to Mn 2+ located at about 641.1 eV, Mn 3+ at about 642.2 eV, and Mn 4+ at about 643.2 eV [ 31–34 ] For all the samples cycled with different potential windows, it can be seen from the XPS spectrum that there are three main valence states of Mn in MnO 2 : Mn 4+ , Mn 3+ , and Mn 2+ . In other words, the MnO 2 ‐based electrode exhibits the changes of valence states of Mn during the electrochemical cycling, and the valence state composition (Mn 4+ , Mn 3+ , and Mn 2+ ) should be dependent on the working potential windows.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that these doping elements can improve the cycle life of the LNMO/Li half cells, but the doped LNMO/graphite full cells deliver a poor cycle life similar to that of the pristine LNMO/graphite cells . Another common solution is to coat LNMO with oxides (e.g., Al 2 O 3 , ZnO, TiO 2 , and Bi 2 O 3 ), phosphates (e.g., AlPO 4 , LiCoPO 4 , and ZrP 2 O 7 ), and Li + ‐ion‐conducting solid electrolytes (e.g., lithium phosphorus oxynitride [LiPON]) . The literature claimed that these coatings on LNMO improve cycle stability of LNMO/Li half cells, but little is known about their impact on LNMO/graphite full cells.…”
Section: Results Of Surface Element Analysis On the Anodes Extracted mentioning
confidence: 99%